Analisis Dampak Inflasi Terhadap Daya Beli Masyarakat di Indonesia - Maysri Handayani Putri Sinaga; Rachel Stephanie Jovanca Nababan; Karisa Kusumadewi Saputri; Abim Khaffi Maulana; Alexander Sabastian Pangaribuan; Muda Harahap, Lokot (LPPM Universitas Buana Perjuangan Karawang, 2026)
Inflation is one of the key indicators in an economy that can influence economic stability as well as public welfare. An increase in the general price level of goods and services may reduce real income, thereby affecting people's ability to meet their consumption needs. This study aims to analyze the impact of inflation on the purchasing power of society in Indonesia. The research employs a qualitative approach using a literature review method by examining various recent scientific journals and relevant studies related to inflation and purchasing power. The findings indicate that inflation has a significant impact on people's purchasing power because rising prices increase household living costs. As a result, households tend to adjust their consumption patterns by reducing spending on non-essential goods and prioritizing basic necessities. The impact of inflation is particularly felt by middle- and lower-income groups since a large proportion of their income is allocated to basic consumption. Therefore, maintaining inflation stability is essential to protect public welfare. Effective inflation control through monetary policy, fiscal policy, and social protection programs plays an important role in maintaining price stability and safeguarding the purchasing power of society.